2007
DOI: 10.1007/s11224-007-9229-z
|View full text |Cite
|
Sign up to set email alerts
|

Borazine: to be or not to be aromatic

Abstract: Aromaticity of borazine, which has been subject of controversial discussions, is addressed. Beside a short review on aromaticity of borazine we report a detailed analysis of two molecular fields, the induced magnetic field (B ind ) and the electron localization function (ELF). The induced magnetic field of borazine shows a long-range shielding cone perpendicular to the molecular plane, as in benzene, but lower in magnitude. Contrary to benzene, borazine shows two weakly paratropic regions, one of them inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
134
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 58 publications
11
134
1
1
Order By: Relevance
“…Very recently Islas et al [94] in their publication entitled Borazine: to be or not to be aromatic based on a detailed analysis of two molecular fields, the induced magnetic field (B ind ) and the electron localization function (ELF) indicated that borazine can be described as a π-aromatic compound but it is not a globally aromatic species, since the delocalized system is not as homogeneous as that of benzene. The induced magnetic field in borazine is weaker than that of benzene but nevertheless pronounced and long-ranged.…”
Section: Predicting the Peculiar Aromaticity Of Borazinementioning
confidence: 99%
“…Very recently Islas et al [94] in their publication entitled Borazine: to be or not to be aromatic based on a detailed analysis of two molecular fields, the induced magnetic field (B ind ) and the electron localization function (ELF) indicated that borazine can be described as a π-aromatic compound but it is not a globally aromatic species, since the delocalized system is not as homogeneous as that of benzene. The induced magnetic field in borazine is weaker than that of benzene but nevertheless pronounced and long-ranged.…”
Section: Predicting the Peculiar Aromaticity Of Borazinementioning
confidence: 99%
“…However, some investigations have shown that borazine may undergo electrophilic substitution in the gas phase under basic conditions much like benzene [1,2]. On the other hand, the aromaticity of borazine has been a controversial matter [3][4][5][6] and most reliable aromaticity criteria advocate non-aromaticity of borazine [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The isoelectronic and isostructural relationship between the BÀN and C=C bond and its consequence on the aromaticity of borazine has been a topic of discussion. [5] From a more applied perspective, borazine serves as a precursor to BN-based ceramic materials.…”
mentioning
confidence: 99%